PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA MODAL DALAM MENUNJANG PERKEMBANGAN BISNIS DAERAH (Studi Kasus Kabupaten/ Kota Di Jawa Timur) - Bakhrudin Bakhrudin; M. Arief Setiawan; Sutrisno Sutrisno (Adbis: Jurnal Administrasi dan Bisnis, 2020)
The purpose of this study was to determine the effect of Regional Original Revenue and General Allocation Funds (DAU) on Regency / City Capital Expenditures in East Java The analysis model in this study uses multiple linear regression analysis, regression analysis is an analysis of the dependence of one dependent variable (bound) on one or more independent variables (free / explanatory). Based on the Regression Test the analysis results obtained both PAD and DAU have a positive regression coefficient, meaning that if there is a positive change in the independent variables (PAD and DAU) will also cause an increase in the value of regional spending. The coefficient of determination is 88.7% The coefficient of determination or R2 Adjusted value of 88.7% indicates that changes in capital expenditure 88.7% can be explained or determined by changes in the independent variables PAD and DAU, while 11.3% is explained by variables outside of PAD and DAU. Significant influence of the independent variables on the dependent variable can be seen from the results of the Fcount 0.00 test which is smaller than the standard tolerable error of α = 5%